Ethical, pedagogical, socio-political and anthropological implications of quaternary prevention - Marc Jamoulle; Michel Roland; Jong-Myon Bae; Bruno Heleno; Giorgio Visentin; Gustavo Diniz Ferreira Gusso; Maciek Godycki-Ćwirko; Miguel Pizzanell; Patrick Ouvrard; Ricardo La Valle; Luis Filipe Gomes; Daniel Widmer; et al. (Sociedade Brasileira de Medicina de Família e Comunidade, 2018)
The concept of quaternary prevention, resulting from a reflection on the doctor-patient relationship, is presented as a renewal of the age-old ethical requirement: first, a doctor must do no harm; second, the doctor must control himself/herself. The origin of the concept, its endorsement by the World Organization of Family Doctors (WONCA) and the European Union of General Practitioners (UEMO), its dissemination, and the debates to which it has given rise, are presented by a panel of authors from 10 countries. This collective text deals more specifically with: the bioethics of prevention, the importance of teaching Quaternary prevention and factual medicine, the social and political implications of the concept of quaternary prevention, and its anthropological dimensions.